Genetic and molecular diversity of Bacillus thuringiensis strains and insecticidal activity potential against Aedes aegypti - Huerta, Doris (2012)
Objectives: To determine the molecular genetic diversity of native B. thuringiensis strains toxic against Aedes aegypti, vector of dengue. Design: Descriptive, analytical study. Setting: Biochemistry and Nutrition Research Center, Faculty of Medicine, San Marcos University, Lima, Peru. Participants: Native and standard strains of B. thuringiensis. Interventions: Extraction of B. thuringiensis genomic DNA from 53 native strains and 10 standard strains isolated from different Peruvian regions soil samples. Diversity was determined by repetitive DNA sequences using REP-PCR technique, visualized in agarose gels stained with ethidium bromide. B. thuringiensis standard and native strains cluster analysis was performed by dendrogram of similarity using bioinformatic programs. Main outcome measures: Diversity of B. thuringiensis strains. Results: Strains from Junin, Huaral, Ica, Cusco, Arequipa, and Cajamarca tended to form groups according to source, highlighting two strains characterized as potentially toxic against Aedes aegypti (Ica and Cajamarca), and outlining a subgroup or cluster with toxic standard strains HD-968 and GM 33. Conclusions: A great diversity of B. thuringiensis native strains coming from different regions of the country have a tendency to form sub-groups according to geographical origin and in relation to standard strains, some of them with a bioinsecticidal potential against B. Thuringiensis, vector of dengue.